A novel inhibitor of activated thrombin activatable fibrinolysis inhibitor (TAFIa) – Part II: Enhancement of both exogenous and endogenous fibrinolysis in animal models of thrombosis - Wang, Yi-Xin; da Cunha, Valdeci; Vincelette, Jon; Zhao, Lei; Nagashima, Mariko; Kawai, Kohichi; Yuan, Shendong; Emayan, Kumar; Islam, Imadul; Hosoya, Junko; Sullivan, Mark E.; Dole, William P.; Morser, John; Buckman, Brad O.; Vergona, Ronald (Thrombosis and Haemostasis, 2007)
We have discovered a novel small-molecule TAFIa inhibitor, BX 528, which is potent, highly selective against other carboxypeptidases and safe. The present study was to determine if BX 528 can enhance exogenous and endogenous thrombolysis in four different animal models. In the first three models, a thrombus was induced by FeCl2 (dogs) or laser (rats) injury of the femoral artery, or formed ex vivo and implanted in the jugular vein in rabbits. A low dose of exogenous t-PA was given to induce a lowlevel thrombolysis on an established thrombus. Co-treatment with BX 528 further enhanced the thrombolytic effects induced by the exogenous t-PA and, thus, r educed thrombosis in all three animal models. In a second rat model, fibrin deposition in the lungs was induced by batroxobin, which was spontaneously resolved in 30 minutes due to the activation of endogenous fibrinolysis. Pre-treatment with lipopolysaccharide (LPS) attenuated this spontaneous fibrinolysis. Co-treatment with 10 mg/kg BX 528 prevented the LPS-induced attenuation of endogenous fibrinolysis. Thus, these studies demonstrated that inhibition ofTAFIa by BX 528, our newly discovered small-molecule TAFIa inhibitor, enhanced both the exogenous (induced by a low dose of t-PA) and endogenous (LPS-induced resistance) thrombolysis without increasing the bleeding risk in four different animal models of thrombosis in different species (rat, dog and rabbit) employing different thrombogenic stimuli (FeCl2, laser, ex vivo and batroxobin) to induce thrombus formation in different tissues (artery, vein and lung microcirculation).
Keywords: TAFI; fibrinolysis; thombolysis; thrombosis; bleeding; rat; dog; rabbit